Financial implications of mobile phone-based personal carbon trading: a case study of Safaricom. (1st July 2021) - Al-Guthmy, Fahd Mohamed Omar; Yan, Wanglin
Abstract: Personal carbon trading (PCT) has garnered significant interest in the literature as an alternative policy instrument to the largely unpopular carbon tax. However, it has been hindered by the cost and administrative complexity concerns as a result of covering potentially millions of emitters. This work expands on a prior study which presented a mobile phone-based PCT scheme for personal road transport in Kenya. In that study, the system design and operation was extensively developed, and distributional impact was assessed using sample data of motorists to identify equity issues. In this extension, I justify the scheme further by assessing the cost concerns using a case study approach of the mobile service provider, Safaricom. Data from the sample survey is revisited and combined with Safaricom's financial reports to simulate the potential cost of the scheme. Results revealed running costs of less than £80 000 annually, several times lower than estimates that relied on the chip card system. Policymakers and researchers are encouraged to build on this scheme's viability as a globally-inclusive variant of PCT.